Identifying profiles of youth characteristics, trajectories of development, and retention factors in a Positive Youth Development program - Timpe, Zachary C., author; Coatsworth, J. Douglas, advisor; Skiba, Hilla, committee member; Lunkenheimer, Erika, committee member; MacPhee, David, committee member (Colorado State University. Libraries, 2017)
Positive Youth Development (PYD) programs are an increasingly common form of intervention for youth of all backgrounds. In particular, PYD programs that take youth "off the streets" while not in school, termed out-of-school time (OST) programs, are of special interest to practitioners and researchers alike due to the diversity of programming available and the ecological contexts they provide. In addition, most youth engage in some form of risky behavior over the course of development, or are exposed to risk factors out of their control. However, PYD programs as a whole have provided little evidence of having meaningful impacts on the youth they serve, and they continually struggle to serve youth from disadvantaged backgrounds or who engage in risky behaviors. These shortcomings potentially result from selection bias that manifests through high attrition rates, which are influenced by many factors, such as a lack of programs to choose from or disinterest in program content. Even when attrition is partially accounted for, evaluating program impacts is difficult, as the processes and outcomes that define PYD remain relatively unclear, including their relation to risk factors. Therefore, in order for PYD programs, and specifically those categorized as OST, to take the next step in increasing and demonstrating the impacts of their programs, additional collaboration and research in a real world context is needed. This dissertation will use data from a PYD program, SOS University, to address two primary research questions. The first study will address the question of, are there specific factors that are associated with youth attrition from PYD programs? This research is timely as prevention scientists have struggled to provide guidance to practitioners on how to minimize attrition rates, a commonly cited impediment to translating scholarly research into real world application. The second study seeks to answer the question, can youth be distinguished into profiles of development characterized by the patterns of responses to PYD indicators? To answer this question, the second study will analyze differences in youth development profiles as they participated in an outdoor leadership program over the course of three years. This study is important in that it has the potential to highlight the positive development that can occur in the context of experiencing or engaging in risk behaviors. The dissertation is organized as follows. Chapter I provides an overview of the existing literature on theory related to PYD and the evidence base for PYD and OST programs. Chapters II and III are studies I and II cited above, respectively. Chapters II and II follow the typical format of an academic manuscript. That is, each chapter will include a more refined literature review that provides an in-depth view of research related to the study at hand, a description of the current study, methods, data analysis approaches and results, and then a discussion. Finally, Chapter IV will be a general discussion of the overall results and how they relate to one another. Additionally, Chapter IV will review overarching strengths and weaknesses of the dissertation, and finally highlight implications that may surface as a result of the studies, including a discourse on future steps that can be taken to increase collaboration between the scientific and applied communities.